2014
DOI: 10.1002/cncr.28685
|View full text |Cite
|
Sign up to set email alerts
|

Young and uninsured: Insurance patterns of recently diagnosed adolescent and young adult cancer survivors in the AYA HOPE study

Abstract: Introduction Young adults have historically been the least likely to have health insurance in the United States. Previous studies of childhood cancer survivors found lower rates of insurance and less access to medical care compared to siblings; however, no studies have examined continuity of insurance after cancer diagnosis in adolescents and young adults (AYAs). Methods Using the AYA Health Outcomes and Patient Experience study, a cohort of 465 15-39 year-olds from participating Surveillance, Epidemiology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 22 publications
(61 reference statements)
1
37
1
1
Order By: Relevance
“…In studies of AYA cancer survivors, health insurance rates have been found to decrease with time from diagnosis (22, 23), particularly for older AYAs and those with less education (23), and a lack of health insurance is a barrier to receiving any medical care (22, 24). Further, more than two-thirds of uninsured survivors have been found to have no personal provider or routine medical care and, even with health insurance, AYA cancer survivors are more likely to forgo medical care due to costs (24).…”
Section: Discussionmentioning
confidence: 99%
“…In studies of AYA cancer survivors, health insurance rates have been found to decrease with time from diagnosis (22, 23), particularly for older AYAs and those with less education (23), and a lack of health insurance is a barrier to receiving any medical care (22, 24). Further, more than two-thirds of uninsured survivors have been found to have no personal provider or routine medical care and, even with health insurance, AYA cancer survivors are more likely to forgo medical care due to costs (24).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AYA patients and survivors face additional financial burdens, and recent results from the Adolescent and Young Adult Health Outcomes and Patient Experience (AYA HOPE) Study reported that 25% of survivors were without health insurance at some time in the first 35 months after their diagnosis. (14)…”
Section: Aya Patients With Cancer Face Unique Issuesmentioning
confidence: 99%
“…While cancer survival among AYAs with many types of cancer is good, above 80%, AYAs have not experienced the same improvements in relative survival as children and older adults for cancers common among AYAs [2, 3]. In addition, AYAs, historically, have had the highest uninsurance rates compared with children and older adults [46]. Furthermore, disparities in cancer survival by race/ethnicity and neighborhood socioeconomic status (SES)—previously well-documented only among older adults—have recently been reported among AYAs [710].…”
Section: Introductionmentioning
confidence: 99%